2017
DOI: 10.1016/j.jsxm.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Amyloid Precursor Protein in Seminal Plasma and Abnormal Penile Sympathetic Skin Response in Lifelong Premature Ejaculation

Abstract: These results showed that patients with lifelong PE had higher APP and Aβ42 levels in seminal plasma. Abnormal PSSR was related to a higher Aβ42 level. Drugs that decrease Aβ could be treatment of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The interactions between peripheral and cerebral neural pathways are involved in the set of neuromuscular events of the ejaculatory reflex (Giuliano, ; Facchinetti et al ., ; Yusof et al ., ). The process of emission is under the control of sympathetic nervous system, which allows the closure of bladder neck and promotes seminal fluid to posterior urethra (Hong et al ., ; Zhang et al ., ,b). The phase of expulsion is controlled by the parasympathetic and somatic nervous system, as well as the perineal muscles (Alwaal et al ., ; Clement & Giuliano, ; Chéhensse et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between peripheral and cerebral neural pathways are involved in the set of neuromuscular events of the ejaculatory reflex (Giuliano, ; Facchinetti et al ., ; Yusof et al ., ). The process of emission is under the control of sympathetic nervous system, which allows the closure of bladder neck and promotes seminal fluid to posterior urethra (Hong et al ., ; Zhang et al ., ,b). The phase of expulsion is controlled by the parasympathetic and somatic nervous system, as well as the perineal muscles (Alwaal et al ., ; Clement & Giuliano, ; Chéhensse et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, PSSR is considered a promising way to study the function of the sympathetic nervous system associated with ejaculation, and abnormal PSSR parameters may indirectly reflect neural dysfunction. Previous studies have shown that sympathetic over‐activity may be another factor involved in the pathological mechanisms of PPE, although potential mechanisms for abnormal PSSR in PE patients are unclear (Xia, Han et al., ; Hong et al., ). In our study, we also examined changes in the patients’ PSSR after dapoxetine treatment because this technique effectively studies of sympathetic system and can easily be used in many countries with any indications.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of studies linking PPE and PSSR, there was a comparative study of the amyloid precursor protein in the seminal fluid of patients with PPE that also measured PSSR, but there are currently no studies available in the literature that assess the effects of drugs on the PPE and PSSR (Hong et al., ).…”
Section: Discussionmentioning
confidence: 99%